A train control system simulation and analysis method. (1st January 2012) - Zhang, Y.; Tang, T.; Zheng, W.; Niu, H.
Experiments in physical and real environment would be expensive, time consuming and unsafe. This project aims to develop a tool to reduce the above mentioned efforts by simulating a whole railway environment, fulfilling the interfaces between subsystems and the elements of these subsystems, testing and analysing the specifications of European Train Control System Level-2 (ETCS L2). UML sequence diagrams and state diagrams are used to model the scenario-based specification and the dynamic behaviours of on-board equipment. The examples of using this method to simulate on-board equipment, test and validate the specifications, as well as the system performance simulation results are also introduced.